Doing action research in your own organization - Coghlan, David (SAGE Publications Ltd, 2014)
Clear, pragmatic and thought-provoking Doing Action Research in Your Own Organization is packed full of practical, expert advice on how to navigate the murky waters of ethics, politics and management in your own organization. Multidisciplinary in its approach to action research the book sets out a step-by-step template for researchers to follow and adapt. Coghlan and Brannick: * Introduce and contextualise action research as an approach * Explore the challenges of doing action research in your own organization * Provide guidance on how to design and implement your insider action research project * Show how to lead change in in your own organization * Demonstrate how your own learning develops through the project * Provide helpful tips on how to disseminate your work The book and its supporting website are the ideal resource for students, researchers and practitioners hoping to generate real change through their action research project and will be particularly relevant to those studying Business and Management, Nursing and Health, Education and Sociology.